Quality of surface water and generation of sludge at water treatment plants - Fiore, Fabiana Alves [UNESP]; Rodgher, Suzelei [UNESP]; Ito, Cristiane Yumi Koga [UNESP]; Bardini, Vivian Silveira Dos Santos [UNESP]; Klinsky, Luis Miguel Gutiérrez (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2020)
Among the waste produced daily by communities are those resulting from the treatment of water for public supply, with local specificities that reflect the characteristics and uses of the land. Despite the continuous generation and inadequate disposal still current in Brazil, there is little information on these residues. The data related to the composition of these sludges are essential for the study of alternatives for beneficial uses and for determining the risks to the environment and human health from inadequate disposal. It is in this context that the present study was developed, with the objective of identifying the physical-chemical characteristics of sludge produced in water treatment plants (WTPs) and of verifying the presence of these elements in the waters of the source used for supply. Such research was carried out through a case study in two WTPs in the state of São Paulo that perform surface abstraction. Therefore, in each of the WTPs, samples of densified sludge, representative of the dry and rainy periods, were characterized. The chemical findings of the sludge have been compared to the historical series of a decade of monitoring of the water quality of the sources of these WTPs. Among the main results, concentrations above the reference limits for the inert residues of aluminum, iron, manganese and barium in sludge are highlighted, as well as the existence of iron and manganese in the raw water collected and the variations in the concentrations of iron, sodium and manganese in the sludge due to the climatic conditions.
Qualidade de água superficial e geração de lodos em estações de tratamento de água
Keywords: Physicochemical parameters; Sludge of WTS; Solid waste; Water quality